PERENCANAAN LUMPUR PEMBORAN BERBAHAN DASAR AIR PADA SUMUR X LAPANGAN Y - Andreas Junianto Andreas Junianto; cahaya rosyidan; bayu satyawira (Jurusan Teknik Perminyakan Fakultas Teknologi Kebumian dan Energi Universitas Trisakti, 2017)
Y Field is a field that located on Sumatera Island. That located at Jambi Province precisely. This X well which will be drilled is a development wells at Y field. All of the draw well in this Y Field is an onshore wells. This X well shall be drilled using water-based mud. This water-based mud is used because it is cheaper and more economical than using oil-based. But, this mud needs tobe added an additive because the water-based mud has a deficiency in controlling the formations of clay. Planning of mud system for X well is using method of the offset wells, that is using around of wells data to be used as a comparison. This first X well drilled for hole section 26” by size of casing 20” with depth up to 150 ft and mud which used is type of gel/water. And then it is continued with hole section 17 ½” by size of casing 13 3/8” with continuing the former mud of drilling in hole section 26”. The depth starts from 150 ft until 1000 ft. The next hole section is 12 ¼” by size of casing 9 3/8” which a depth that starts from 1000ft until 4100 ft and using new of mud with polymer mud. Last hole section 8 ½” without casing and using polymer mud to continuing the previous drilling from the depth of 4100 ft until 4900 ft. Problem that faces by this draw well is the presence of faults and high pressure at depths below 1000 ft, so it needs to be prepared LCM (Loss Control Material) and Jumbo Bag to overcome the occurrence of kick.